Dilute acid pretreatment of sorghum biomass to maximize the hemicellulose hydrolysis with minimized levels of fermentative inhibitors for bioethanol production - Deshavath, Narendra Naik (3 Biotech, 2017)
Conversion of lignocellulosic biomass into monomeric carbohydrates is economically beneficial and suitable for sustainable production of biofuels. Hydrolysis of lignocellulosic biomass using high acid concentration results in decomposition of sugars into fermentative inhibitors. Thus, the main aim of this work was to investigate the optimum hydrolysis conditions for sorghum brown midrib IS11861 biomass to maximize the pentose sugars yield with minimized levels of fermentative inhibitors at low acid concentrations. Process parameters investigated include sulfuric acid concentration (0.2–1 M), reaction time (30–120 min) and temperature (80–121 °C). At the optimum condition (0.2 M sulfuric acid, 121 °C and 120 min), 97.6% of hemicellulose was converted into xylobiose (18.02 mg/g), xylose (225.2 mg/g), arabinose (20.2 mg/g) with low concentration of furfural (4.6 mg/g). Furthermore, the process parameters were statistically optimized using response surface methodology based on central composite design. Due to the presence of low concentration of fermentative inhibitors, 78.6 and 82.8% of theoretical ethanol yield were attained during the fermentation of non-detoxified and detoxified hydrolyzates, respectively, using Pichia stipitis 3498 wild strain, in a techno-economical way. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13205-017-0752-3) contains supplementary material, which is available to authorized users.